2014
DOI: 10.1002/smll.201303680
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Graphene Growth on Metal Surfaces: Theoretical Perspectives

Abstract: Graphene is an important material with unique electronic properties. Aiming to obtain high quality samples at a large scale, graphene growth on metal surfaces has been widely studied. An important topic in these studies is the atomic scale growth mechanism, which is the precondition for a rational optimization of growth conditions. Theoretical studies have provided useful insights for understanding graphene growth mechanisms, which are reviewed in this article. On the mostly used Cu substrate, graphene growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
96
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 120 publications
(231 reference statements)
1
96
0
Order By: Relevance
“…Several notable findings have been reported already [19][20][21][22][23][24][25][26]: Carbon monomers reside stably at subsurface sites of copper [19], and they form a metal bridged intermediate prior to producing a carbon-carbon bond [20]; The carbon clusters in the earlier nucleation stage take linear forms rather than ring structures [24]; The graphene edges are terminated not only by surface copper atoms but also by additional copper ad-atoms, which may facilitate carbon atom reactions at graphene edges [23]; Carbon monomers can diffuse in the copper subsurface, but a surface terminated graphene edge blocks the diffusion, leading to the carbon atom incorporation to the edge [25]. (Theoretical studies are reported for the precursor decomposition processes as well, see refs.…”
Section: Introductionmentioning
confidence: 88%
“…Several notable findings have been reported already [19][20][21][22][23][24][25][26]: Carbon monomers reside stably at subsurface sites of copper [19], and they form a metal bridged intermediate prior to producing a carbon-carbon bond [20]; The carbon clusters in the earlier nucleation stage take linear forms rather than ring structures [24]; The graphene edges are terminated not only by surface copper atoms but also by additional copper ad-atoms, which may facilitate carbon atom reactions at graphene edges [23]; Carbon monomers can diffuse in the copper subsurface, but a surface terminated graphene edge blocks the diffusion, leading to the carbon atom incorporation to the edge [25]. (Theoretical studies are reported for the precursor decomposition processes as well, see refs.…”
Section: Introductionmentioning
confidence: 88%
“…The insights on graphene growth on Cu at the atomic level, mainly with theoretical calculations, have been reviewed by Wu et al [18] Although there are still a lot of unknown details, in general, …”
Section: Growth Kinetics and Toward Synthesis Of Large-area Graphene mentioning
confidence: 99%
“…The interest of the material's science community in carbon monomers (C1) and dimers (C2) has grown considerably in the last years because of their role in the synthesis of high-quality graphene (Gr) monolayers on solid surfaces [1][2][3] . Carbon clusters, especially those formed by a small number of atoms, play an important role in determining the different atomistic mechanisms for the epitaxial growth of graphene by means of chemical vapor deposition (CVD).…”
Section: Introductionmentioning
confidence: 99%